2022
DOI: 10.3390/antibiotics11111626
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use and Stewardship Indicators in the First- and Second-Level Hospitals in Zambia: Findings and Implications for the Future

Abstract: Introduction: There are increasing concerns with growing rates of antimicrobial resistance (AMR) across Africa, including in Zambia, enhanced by inappropriate utilization of antibiotics across the sectors. There is a need in hospitals to document current prescribing patterns via point prevalence surveys (PPS) alongside recognized indicators to improve future use. The findings can subsequently be used to develop and instigate appropriate antimicrobial stewardship programs (ASPs) to improve the quality of future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 88 publications
3
11
2
Order By: Relevance
“…Antimicrobial utilization was typically high across most of the studied African countries (over 50% of patients), with similar rates in a recent study in Zambia [147]. Hospitals in Nigeria saw the highest antimicrobial utilization rates at 59.6-97.6% of in-patients surveyed Table 1.…”
Section: Current Antimicrobial Utilization Patterns In Hospitals Acro...supporting
confidence: 75%
“…Antimicrobial utilization was typically high across most of the studied African countries (over 50% of patients), with similar rates in a recent study in Zambia [147]. Hospitals in Nigeria saw the highest antimicrobial utilization rates at 59.6-97.6% of in-patients surveyed Table 1.…”
Section: Current Antimicrobial Utilization Patterns In Hospitals Acro...supporting
confidence: 75%
“…This use of 3GCs in primary care facilities promotes the emergence of 3GC-resistant pathogens thereby further limiting treatment options for patients being referred to tertiary hospital where 3GCs are widely used as empiric treatment [36]. Similar to the findings at the UTH and the primary care facilities in Lusaka [35,36], another study in Zambia that reviewed antibiotic use and stewardship indicators in the first-and second-level hospitals in ten provinces at ten different hospitals found the prevalence of antibiotic use among the in-patients to be at 59% with a high rate of empiric prescribing (97%), of which ceftriaxone was 36% of all antibiotics prescribed [37]. Low compliance to the national standard treatment guidelines (STGs), low justified antibiotic use at 16% and only 3% of the treatment having been guided by microscopy, culture and sensitivity (MCS).…”
Section: Plos Global Public Healthmentioning
confidence: 79%
“…Low compliance to the national standard treatment guidelines (STGs), low justified antibiotic use at 16% and only 3% of the treatment having been guided by microscopy, culture and sensitivity (MCS). Practices that drive the emergence of AMR [37].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…From the Zambian point of view, implementation of the AWaRe tool is still in its infancy, but hospitals where prescribers adhered to this AMS strategy reported low AMR challenges. 7 Therefore, the political will demonstrated by the Government of the Republic of Zambia to support the implementation of this AMS strategy will further prevent and reduce AMR cases.…”
Section: Prior Successes Of the Who Aware Toolmentioning
confidence: 99%
“…In Zambia, there are gaps and lack of knowledge among healthcare workers on the use the AWaRe tool because studies have reported high prescribing of Watch antibiotics. 7 , 8 , 10 In all studies, ceftriaxone, a Watch antibiotic, was being overused (Table 1 ). This contrasts with the WHO recommendations.…”
Section: Experiences In Zambia On the Use Of The Aware Classification...mentioning
confidence: 99%